Studies in vitro and in vivo of thymidine analog labeled with organometalic complex of technetium-99m for potential use in tumor diagnosis (Revista Brasileira de Ciências Farmacêuticas, 2008)
Thymidine analogs have been labeled with different radioisotopes due to their potential in monitoring the uncontrollable cell proliferation. Considering that the radioisotope technetium-99m still keeps a privileged position as a marker due to its chemical and nuclear properties, this work was designed to develop a new technique of labeling of thymidine analog with 99mTc, by means of the organometallic compounds. The aims of this research were: synthesis of the organometallic precursor technetium-99m-carbonyl, thymidine labeling with this precursor, study of stability, and radiochemical e biological evaluation with healthy and tumor-bearing animals. The organometallic precursor and the labeling of thymidine with this precursor were resulted with a radiochemical pureness of >; 97% and >; 94%, respectively, with good radiochemical stability up to 6 h in room temperature. The cysteine and histidine challenge indicated losses between 8 and 11% for concentrations until 300 mM. The biodistribution assay in healthy mice revealed rapid blood clearance and low uptake by general organs with renal and hepatobiliary excretion. The tumor concentration was of 0.28 and 0.18 %ID/g for lung and breast cancer, respectively. The results imply more studies in other thymidine analogs.